The China crisis : how China's economic collapse will lead to a global depression - Gorrie, James R. (Hoboken, New Jersey : Wiley, 2013)
A controversial look at the impending Chinese economic collapse-the history behind it, its contemporary causes, and its dire implications for the global economy All the experts agree: the 21st century belongs to China. Given America's looming insolvency and the possibility of the collapse of the U.S. dollar, who can doubt that China is poised to take over the role of economic superpower? Written by political economist and leading financial journalist James Gorrie, this book offers a highly controversial, contrarian view of contemporary China. Drawing upon a wealth of historical and up.
Introduction -- A World on Edge -- Stability and Legitimacy : A Chinese Crisis from Within -- The Rising Tide of Instability -- Is China's Economy Sustainable? -- China's Quiet Crisis : Financial and Economic Meltdown -- China's Extreme Environmental Degradation -- Political Transition and the Breaking Point -- Empire Decline and Complexity Theory -- The Fall of the Red Dragon.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Since 2000; Global Financial Crisis, 2008-2009.; BUSINESS & ECONOMICS -- Economic Conditions; BUSINESS & ECONOMICS -- Economic History; BUSINESS & ECONOMICS -- Economics -- Comparative; POLITICAL SCIENCE -- Economic Conditions; Economic history; Economic policy; China -- Economic conditions -- 2000-; China -- Economic policy -- 2000-; China; Electronic books; Electronic books